Governance Through Trading and Intervention: A Theory of Multiple Blockholders - Edmans, Alex; Manso, Gustavo (Review of Financial Studies, 2011)
[Traditional theories argue that governance is strongest under a single large blockholder, as she has high incentives to undertake value-enhancing interventions. However, most firms are held by multiple small blockholders. This article shows that, while such a structure generates free-rider problems that hinder intervention, the same coordination difficulties strengthen a second governance mechanism: disciplining the manager through trading. Since multiple blockholders cannot coordinate to limit their orders and maximize combined trading profits, they trade competitively, impounding more information into prices. This strengthens the threat of disciplinary trading, inducing higher managerial effort. The optimal blockholder structure depends on the relative effectiveness of manager and blockholder effort, the complementarities in their outputs, information asymmetry, liquidity, monitoring costs, and the manager's contract.]